2015
DOI: 10.5312/wjo.v6.i11.996
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative outcomes in minimally invasive lumbar spine surgery: A systematic review

Abstract: AIM:To compare minimally invasive (MIS) and open techniques for MIS lumbar laminectomy, direct lateral and transforaminal lumbar interbody fusion (TLIF) surgeries with respect to length of surgery, estimated blood loss (EBL), neurologic complications, perioperative transfusion, postoperative pain, postoperative narcotic use, and length of stay (LOS). METHODS:A systematic review of previously published studies accessible through PubMed was performed. Only articles in English journals or published with English … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 63 publications
1
20
0
Order By: Relevance
“…Modern anatomic descriptions typically list the innervation of the PMM as primarily from L1 and L2 (Dakwar et al, 2011a;Ahmadian et al, 2013) (Table 2). In recent anatomical studies, significant attention has been given to the relationship of the PMM to nerves of the lumbar plexus (Skovrlj et al, 2015) or uncommon anatomic variations (Cahill et al, 2012), rather than to the nerves supplying the muscle itself. However, a recent study aimed at establishing landmarks for percutaneous injection found "multiple" nerve branches to the psoas major, yielding an average of 3.7 branches per psoas major (Van Campenhout et al, 2010).…”
Section: Prior Anatomical Depictionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Modern anatomic descriptions typically list the innervation of the PMM as primarily from L1 and L2 (Dakwar et al, 2011a;Ahmadian et al, 2013) (Table 2). In recent anatomical studies, significant attention has been given to the relationship of the PMM to nerves of the lumbar plexus (Skovrlj et al, 2015) or uncommon anatomic variations (Cahill et al, 2012), rather than to the nerves supplying the muscle itself. However, a recent study aimed at establishing landmarks for percutaneous injection found "multiple" nerve branches to the psoas major, yielding an average of 3.7 branches per psoas major (Van Campenhout et al, 2010).…”
Section: Prior Anatomical Depictionsmentioning
confidence: 99%
“…Minimally invasive spinal surgical techniques have become increasingly popular because of the interest in avoiding muscular disruption and possible muscular atrophy; these techniques have been shown to decrease blood loss and reduce hospital length of stay (Wang et al, 2011;Waschke et al, 2014;Skovrlj et al, 2015). Minimally invasive lateral approaches to the spine involve intramuscular dissection of both the flank wall as well as the psoas major muscle (PMM) to gain access to spinal pathology, most commonly that involving the intervertebral (IV) disc or the vertebral body.…”
Section: Introductionmentioning
confidence: 99%
“…15,16 Minimally invasive spine surgery has shown benefits such as lesser iatrogenic injury to the paravertebral muscles, decreased intraoperative bleeding, decreased complications associated with the surgical wound, lower consumption of narcotics for control of postoperative pain, shorter hospital stays, and resumption of daily activities in less time compared with conventional surgery. 17 In the technique presented here, only a small medial portion of the occipital tendon of the semispinalis capitis muscle, and the occipital and vertebral insertion of the posterior minor rectus capitis muscle were detached to reach the atlanto-occipital space. The remainder of the extensor neck muscles were preserved.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to the first criteria, a review by Skovrlj et al compared the minimally invasive versus the open procedure for laminectomy, TLIF, and direct lateral interbody fusion (DLIF). The authors reported MISS to be as effective as the analogous open procedures [ 10 ]. With respect to the second criteria, MISS procedures have also been shown to decrease injury to the multifidus muscle [ 2 ], decrease physiologic stress [ 11 ], as well as maintain the biomechanical properties of the spine [ 12 ].…”
Section: Introductionmentioning
confidence: 99%